Intuitive analog circuit design : a problem-solving approach using design case studies - Thompson, Marc T. (Elsevier Newnes, 2006)
This book reflects Dr. Thompson's twenty years of experience designing and teaching analog circuit design, and is an outgrowth of course notes from his graduate-level analog circuit design course taught at Worcester Polytechnic Institute entitled "Analog Circuits and Intuition." In this class, he describes intuitive and "back of the envelope" techniques for designing and analyzing analog circuits, including transistor amplifiers (CMOS and bipolar), transistor switching, thermal circuit design, magnetic circuit design, control systems, and the like. The application of some simple rules-of-thumb and design techniques is the first step in developing an intuitive understanding of the behavior of complex electrical systems. This book outlines some ways of thinking about analog circuits and systems that hopefully develops such "circuit intuition" and a "feel" for what a good, working analog circuit design should be. *Introduces analog circuit design with a minimum of mathematics. *Gives readers an intuitive "feel" for analog circuit operation and rules-of-thumb for their design. *Uses numerous analogies from digital design to help readers whose main background is in digital make the transition to analog design. *Accompanying CD-ROM contains PowerPoint presentations for each chapter and MATLAB files used in the text